Analisis Pengaruh Suhu Preheating 125˚C, 150˚C Dan 200˚C Hasil Pengecoran Logam Terhadap Terjadinya Hot Tearing Menggunakan Material Alumunium 6061 - Haris, Emin; Van Gunawan, Leo; Luthfi, Muhammad; Rakhman, Abdul (Indonesian Society of Applied Science, 2024)
The aluminum casting industry has experienced a lot of innovation and creativity to maintain its existence. Metal casting is a process by which hot molten metal is poured into a mold containing hollow pieces or cavities of the desired finished shape. The process of casting with a permanent mold is preheating the casting mold before the casting process is carried out. This is done so that the temperature of the casting mold increases, so that the difference between the temperature of the mold and the temperature of the aluminum to be poured is not too great. This study aims to overcome or prevent hot tearing by increasing the preheating temperature in the mold. The test results show that the preheating temperature of 200ºC does not experience shrinkage in the metal casting results. Whereas at preheating temperatures of 125ºC and 150ºC there are hot tearing defects and there is shrinkage. whereas at the preheating temperature variation of 200ºC there are only shrinkage defects. The results of the vickers hardness test showed that the higher the preheating temperature, the hardness value of the casting product will increase. The highest vickers hardness value was obtained at the 200°C preheating temperature variation of 69.55 HV, while at the 150°C preheating temperature variation, the vickers hardness value was 68.51 HV. and at a variation of the preheating temperature of 125ºC, the vickers hardness value is 67.04 HV. The results obtained from metallographic testing are aluminum 6061. Judging from the microstructure at the 200℃ preheating variation, the dentite grains look smaller than the 125℃ preheating variation and the 150℃ preheating variation. It can be concluded that the higher the preheating temperature, the better the denrite density.